The Impact of Economic related Outcomes on the Sustainable Energy Technologies in Top Ten Asian Countries - Khan, Aisha; Salim , Ansa Savad; Pantamee, Abdurrahman Adamu; Tufail, Bushra (Transformations In Business & Economics, 2025)
In terms of maintaining sustainable economic growth, Asian economies share the issues of other developed economies. However, regardless of its status, the region bears the burden of being a high emitter of carbon due to over exploitation of non-renewable resources. The area can maintain its environmental status by switching to renewable energy sources. From 2008 to 2020, this research examines the effects of renewable energy sources on the economy of several Asian countries. Covariate augmented Dickey-Fuller (CADF) and cross-sectional augmented IPS (CIPS) tests for unit root, together with the continuously updated bias-corrected (CUP-BC) and updated full modified (CUP-FM) estimators, are used by researchers to evaluate the correlations. There is a favourable association between producing renewable energy and financial profits, according to the data. Policymakers in the chosen nations should take FDI and GDP into account as important measures of sustainable technology, according to the results. Renewable energy technology might be developed by government agencies in collaboration with the business sector and information and communication technologies (ICT) in order to reduce their dependency on potentially hazardous resources.